Efektivitas Program Digitalisasi Pelayanan Publik Di Desa Tongke-Tongke (Studi Kasus: Program Layanan Mandiri Desa) - Sahrung Sahrung; Mukrimah Mukrimah; Fitriani Fitriani; Kiki Rasmala Sani (Journal of Innovative and Creativity, 2025)
Digital transformation in the public service sector has become a strategic step to enhance the efficiency and quality of services to the community, including at the village level. This study aims to analyze the effectiveness of the Layanan Mandiri (Self-Service Program) in Tongke-Tongke Village, Sinjai Timur District, Sinjai Regency, as a form of digitalized public service. This research uses a qualitative approach with data collection techniques including observation, interviews and documentation. Data analysis refers to Budiani's effectiveness theory, which includes four key indicators: target accuracy, level of program socialization, goal achievement, and program monitoring. The findings show that although the self-service system is technically available and operational, its utilization has not yet reached all community groups. The service is mostly used by tech-literate individuals, while vulnerable groups such as the elderly are still not optimally engaged. Furthermore, program socialization remains limited, and the main objective—enabling administrative services to be accessed from home—has not been fully realized, as most residents still prefer to visit the village office directly. In addition, program monitoring is not yet conducted systematically. Thus, the effectiveness of the Layanan Mandiri program in Tongke-Tongke Village is still suboptimal and requires improvements in socialization, digital literacy, and ongoing evaluation.